Development of the Concept vs Prototyping: Implementation of a real scale Water-Energy Integrated System - Silva, Ana Rita (2018)
Currently, the concept of smart cities and renewable energy are more consolidated and developed. With each passing day, new technological advances are emerging within both themes. At the same time, the water sector has becoming increasingly demanding in terms of quality and compliance with all existing legislation. That said, it is understandable that both sectors and their management entities come together in search of more sustainable operations that go against the reduction of greenhouse gas emissions, decentralization of energy production and the improvement of efficiency, quality and use of resources. It is important to understand the synergies between water and energy to contradict what has been said so far about the increasing demand for energy, its exponential trend and the negative repercussions on freshwater resources. As such, this article aims to address the interconnection between both sectors to promote alternative scientific and technological improvements to the management and development of Integrated Water-Energy systems, while studying the dynamics between the theoretical development of the problem and the challenges of prototyping of such complex systems in real and urban context.